KAJIAN LITERATURE: DAMPAK PERKEBUNAN KELAPA SAWIT TERHADAP LINGKUNGAN DALAM PERSPEKTIF AMDAL - Widia Putri Febriani; Nabil Sasgita; Gepri (Hiradika | Hira Institute, 2025)
Oil palm (Elaeis guineensis) is one of the leading commodities that supports the national economy. Despite its numerous benefits, oil palm expansion also presents a number of challenges. The government requires the preparation of an Environmental Impact Analysis (AMDAL) as an environmental management instrument. However, the effectiveness of AMDAL remains questionable. This study aims to analyze various literature related to the environmental impacts of oil palm plantations and analyze the role and effectiveness of AMDAL in mitigating these impacts. The literature review method uses a descriptive-analytical approach. Data were obtained from relevant scientific journals, books, and government reports from the past 10 years. The literature review was conducted on 10 relevant articles. The results of the literature review indicate that oil palm plantations provide economic and social benefits, but also have negative impacts on the environment and local culture. AMDAL serves as a mitigation instrument whose effectiveness depends on implementation, monitoring, and community participation. Therefore, strengthening policies and sustainable management are necessary to balance the economy, environment, and social welfare.